The Immunohistochemical Expression of Vascular Endothelial Growth Factor in Gastrointestinal Stromal Tumor. A Clinicopathological Study. - Al-Khafaji, Khitam R. (Journal of the Faculty of Medicine Baghdad, 2014)
Back ground: Gastrointestinal Stromal Tumors (GISTs), although are rare, are the most common mesenchymal tumors of the digestive system. Vascular endothelial growth factor(VEGF) is associated with the malignant potential of several types of carcinomas.Patients, material, and methods: This is a retrospective study including thirty two randomly selected cases of GISTs collected from the pathology laboratory of the gastroenterology and hepatology teaching hospital and from private laboratories from the period January 2010 to December 2013. VEGF immunohistochemical marker was applied to the tumor tissue sections to evaluate its expression and to correlate it with other parameters.Objectives: to evaluate the expression of VEGF in GIST and its correlation with different clinic- pathologic parameters and risk categories.Results:  The mean age of the patient was 42.5 years with a female to male ratio of 1.3:1. The stomach was the most common site for the tumor. VEGF was expressed in 12(37.5%) cases. There was a significant statistical correlation between overexpression of VEGF and the patients' gender and the primary tumor site. There was no significant statistical correlation between VEGF overexpression and age of the patients, size of the tumor, mitotic index, and risk of malignant potential categories.Conclusion: There is a significant statistical correlation between VEGF expression and both gender of the patients, and the primary site of GIST.